1996
DOI: 10.1126/science.271.5248.515
|View full text |Cite
|
Sign up to set email alerts
|

Altered Reactivity of Superoxide Dismutase in Familial Amyotrophic Lateral Sclerosis

Abstract: A subset of individuals with familial amyotrophic lateral sclerosis (FALS) possesses dominantly inherited mutations in the gene that encodes copper-zinc superoxide dismutase (CuZnSOD). A4V and G93A, two of the mutant enzymes associated with FALS, were shown to catalyze the oxidation of a model substrate (spin trap 5,5'-dimethyl-1-pyrroline N-oxide) by hydrogen peroxide at a higher rate than that seen with the wild-type enzyme. Catalysis of this reaction by A4V and G93A was more sensitive to inhibition by the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
371
3
3

Year Published

1996
1996
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 683 publications
(387 citation statements)
references
References 22 publications
9
371
3
3
Order By: Relevance
“…Transgenic mouse models of ALS expressing mutant human SOD1 support human studies showing increased oxidative damage to mitochondrial proteins, lipids and DNA (reviewed in Barber and Shaw 2010). This has been explained by excessive dismutase activity of mutant SOD1 (Goldsteins et al 2008;Wiedau-Pazos et al 1996), increased levels of ROS produced by mitochondria following inhibition of complex I (Kruman et al 1999;Mattiazzi et al 2002;Murphy 2009;Zimmerman et al 2007), or increased NADPH oxidase (NOX) activity through mutant SOD1 interacting with Rac1, a NOX regulator (reviewed in Boillee and Cleveland 2008). It should be noted, however, that recent data indicate that overexpression of mutant SOD1 G93A in yeast cells actually provided increased protection against respiration-derived ROS (Kloppel et al 2010).…”
Section: Mitochondrial Morphological Abnormalities and Dysfunctions Imentioning
confidence: 95%
“…Transgenic mouse models of ALS expressing mutant human SOD1 support human studies showing increased oxidative damage to mitochondrial proteins, lipids and DNA (reviewed in Barber and Shaw 2010). This has been explained by excessive dismutase activity of mutant SOD1 (Goldsteins et al 2008;Wiedau-Pazos et al 1996), increased levels of ROS produced by mitochondria following inhibition of complex I (Kruman et al 1999;Mattiazzi et al 2002;Murphy 2009;Zimmerman et al 2007), or increased NADPH oxidase (NOX) activity through mutant SOD1 interacting with Rac1, a NOX regulator (reviewed in Boillee and Cleveland 2008). It should be noted, however, that recent data indicate that overexpression of mutant SOD1 G93A in yeast cells actually provided increased protection against respiration-derived ROS (Kloppel et al 2010).…”
Section: Mitochondrial Morphological Abnormalities and Dysfunctions Imentioning
confidence: 95%
“…In some familial ALS cases, mutations to the C u binding site of CdZn superoxide dismutase (SOD; superoxide oxidoreductase, EC 1.15.1 . l ) may increase the level of Cu-associated toxicity in motor neurons (Wiedau-Pazos et al, 1996;Yim et al, 1996;Ghadge et al, 1997;Zu et al, 1997).…”
mentioning
confidence: 99%
“…It has been reported that the FALS mutants, G93A and A4V, exhibits an enhanced free radicalgenerating activity, while its dismutation activity is identical to that of the wild-type enzyme [12][13][14]. Previous results showed that the hydroxyl radical was generated in the reaction of human Cu,Zn-SOD with H202 [ 15].…”
Section: Resultsmentioning
confidence: 99%